Characterization of Sn doped vanadium oxide thin films for nonlinear optical applications. (2021) - Yadav, Sandeep; Kumari, Sonia; Bala, Renu; Gagandeep,; Thakur, Rajesh; Mohan, Devendra
Abstract: Tin doped vanadium oxide thin films were deposited on the glass substrate by thermal evaporation technique with 3%, 6%, 9% and 12% by weight of SnO2 . The deposited films were characterized by X-ray diffraction (XRD), energy dispersive X-ray (EDX) spectrometer, atomic force microscopy (AFM) and UV-Vis spectroscopy. The amorphous nature of all deposited films was confirmed by the X-ray diffraction method. The elemental analysis of the films was confirmed by EDX analysis. UV–Vis spectroscopy is used for optical analysis such as optical transmission, absorption and band gap analysis of the thin films in the range 300–800 nm. The nonlinear optical parameters of the deposited thin films were estimated by empirical relations. Based on all these characterizations, the films are practical for linear and nonlinear applications.